Connecting Landscapes - T. SWAPNA; T. JHANSI; K. SUNITHA RANI (The Bioscan, 2025)
This thesis explores the potential of enhancing connectivity between the riverfronts of the Krishna and Paleru Rivers through integrated urban design strategies. Situated in an area of rich cultural heritage and natural beauty, this study aims to create a cohesive riverfront experience that fosters ecological preservation, social interaction, and economic development. The research will investigate ways to connect fragmented urban spaces, improve public access, and incorporate green infrastructure, creating a sustainable and resilient urban environment.